(untitled) (Research, Society and Development, 2025)
As an educational and pedagogical tool, the school garden enables the integration of enriching information for students, especially in the context of Environmental Education, which is essential in forming students who are aware of current environmental protection issues and quality of life. This research aimed to implement a school garden as a pedagogical tool for practical Environmental Education classes with students in the 1st year of the technical course in Environment. The study was developed at the Professor Francisco de Assis Pedrosa State Center for Professional Education (CEEP) in Mossoró/RN in April 2024, with the cultivation of vegetables such as coriander, lettuce, and chives. Initially, the land was cleared, followed by the preparation of the beds, fertilization, and planting. The organic fertilizers used were eggshell powder, coffee grounds, manure, leaf litter, and bone meal. With the development of the practical Environmental Education classes, it was possible to observe the student’s performance throughout the construction and development of the garden. The students observed, questioned, and suggested improvements in the management and cultivation of vegetables and also sought ways to work on sustainability beyond the school environment, thus adding positive results to the environment. Therefore, the student’s performance, creativity, and knowledge regarding developing and managing the vegetable garden were remarkable. The work showed that this pedagogical tool enables the relationship between teaching and learning of students in issues related to the environment since the practical classes effectively assimilated the students with the subject of Environmental Education.